2019
DOI: 10.1111/ijfs.14084
|View full text |Cite
|
Sign up to set email alerts
|

Impact of processing on polysaccharides obtained from button mushroom (Agaricus bisporus)

Abstract: Agaricus bisporus fruiting bodies were subjected to processing: blanching, boiling in water and blanching followed by lactic acid fermentation. Water soluble polysaccharides were obtained from fruiting bodies, quantified and analysed in terms of chemical composition, antioxidant capacity and antiproliferative activity towards cancer cell lines (MCF-7 and T-47D). The content of water soluble polysaccharides ranged from 7.35 AE 0.12 to 6.90 AE 0.17 mg g À1 fresh weight of sample. Boiling in water and blanching f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…In contrast, the level of carbohydrate markedly rose reaching 93.00 ± 3.59%. These data is in accordance with previous experiment conducted on Agaricus bisporus [22]. The loss of protein and phenolics during lactic acid fermentation of mushrooms can be attributed to enzymes that are produced by bacteria: proteases degrading protein moieties [39] and esterases which release phenolic compounds [40].…”
Section: Chemical Characteristics Of Water Soluble Polysaccharidessupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, the level of carbohydrate markedly rose reaching 93.00 ± 3.59%. These data is in accordance with previous experiment conducted on Agaricus bisporus [22]. The loss of protein and phenolics during lactic acid fermentation of mushrooms can be attributed to enzymes that are produced by bacteria: proteases degrading protein moieties [39] and esterases which release phenolic compounds [40].…”
Section: Chemical Characteristics Of Water Soluble Polysaccharidessupporting
confidence: 92%
“…Blanching did not cause statistically relevant changes, whereas boiling led to the increase in the amount (112.0 ± 2.0 mg/g dw). The observed increase in the case of boiled fruiting bodies is with agreement with the previous study conducted on Hypsizygus marmoreus fungi [32] or button mushroom [22]. The reason for this could be the leaking of easy soluble substances into the brine and changing the ratio between high and low weight molecular weight compounds.…”
Section: The Content Of Water Soluble Polysaccharidessupporting
confidence: 91%
See 1 more Smart Citation
“…The molecular weight of endo‐polysaccharide obtained from P. igniarius was estimated 1.5 kDa by HPGPC and dextran standards were used for calibration ranging from 5.2 to 1,482 kDa (Zhang, Ma, et al, ). Radzki et al () purified a water‐soluble polysaccharide from Agaricus bisporus , confirmed the molecular weight as 1.9 kDa using gel permeation chromatography and according to the calibration curve prepared with pullulans. The molecular weight of water‐soluble polysaccharide was extracted from the spores of G. lucidum was calculated as 8,000 Da.…”
Section: Resultsmentioning
confidence: 99%
“…Yeast in fermented bread possesses a cell wall that is composed of alpha‐mannan (mannose polysaccharide), which is large enough to activate the pathway of microbial community members to degrade it (Cuskin et al., 2015). Apart from yeast (and beer) in bread, the mushroom is also a major source of fungi in human diets, whose cell walls are rich in beta‐glucan and chitin (Radzki et al., 2019). Prulan is an alpha‐1,6‐linked malt trisaccharide polymer generated by Aureomyces pullulans.…”
Section: Carbohydrates In the Intestinementioning
confidence: 99%